An exploration of young women's perceptions and experiences of participating in HIV prevention vaccine clinical trials in Nyanga Township in the Western Cape, South Africa - Nandudu, Norah (University of Cape Town, 2015)
HIV and AIDS has severely inflicted suffering on the global population and reported to be the worst killer disease in sub-Saharan Africa. Preventive measures such as condom use among young people is still low and less effective in preventing the spread of the disease, it was recommended by the United Nations General Assembly Special Session on HIV and AIDS (2001) to accelerate the development of HIV vaccine aimed at curbing the disease. This study sought to explore young women’s experiences and perceptions about HIV prevention vaccine clinical trials so as to inform the design and implementation of vaccine trials in Africa. The study employed purposive sampling to interview 27 participants using semi-structured interview schedule. A tape recorder was used to capture data and coding procedures were used to analyze data. Findings drawn from participants’ responses and compared with literature from previous studies on vaccine trials and social development theories indicate that participants decide to join HIV prevention vaccine clinical trials because they hope to be protected from HIV infection. Most importantly participants hope to get access to medical care and treatment, meanwhile some participants perceived HIV vaccines harmful to humans hence they usually decline to participate. The study also identified study participation challenges related to socio-cultural and historical aspects. Although vaccines have had some success stories in the prevention and control of infectious diseases such as the eradication of polio, smallpox and measles, prevailing challenges need to be addressed if vaccine development is to be feasible. Providing more information, reinforcement of community awareness and mobilization around issues of HIV vaccine clinical trials at all levels of vaccine design and implementation is required to ensure appropriateness and acceptability of vaccine trial participation.